Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Usahatani Kentang Di Kabupaten Bener Meriah Provinsi Aceh - Mawardati, Mawardati (Agrium, 2013)
This study was conducted in a potato farm in Bener Meriah District of Aceh Province from June to August 2013. The purpose of this study was to determine the factors that affect potato farm income in the observation site. The analytical method used is the method of multiple linear regression analysis. The analysis showed that the amount of production, land, labor, capital and the selling price is very significant influence on a potato farm in the area.